Stress levels in family farmers: a study in the municipality of Araçatuba-SP - Pereira, Fernanda Cristina [UNESP]; Filho, Luís Roberto Almeida Gabriel [UNESP]; Baptista, Renato Dias [UNESP] (Centro Universitario de Maringa, 2024)
The work of family farmers has been considered an activity with a high potential for triggering stress due to the multiplicity of roles linking professional and family life, execution in adverse environmental conditions, and various unpredictable factors. Stress is an interdisciplinary concept and is understood as an evaluative process that triggers psychophysiological responses aimed at adapting a person to situations perceived as stressful and which can trigger various physical and psychological illnesses. Given this context, this article aimed to identify stress levels and the prevalence of physical and psychological symptoms in family farmers in Araçatuba-SP. This is a cross-sectional, applied study with an exploratory, descriptive objective and a survey. The following instruments were used to collect data: Lipp's Inventory of Stress Symptoms for Adults (ISSL) and a sociodemographic questionnaire. The results showed that most of the sample had mild and moderate stress levels.
Níveis de estresse em agricultores familiares: um estudo no município de Araçatuba-SP
Keywords: Family farming; Occupational stress; Stress